Multidetector computed tomography (MDCT) estimation of prevalence and anatomic characteristics of the sternal body foramen in the population of central Serbia - Vulović, Maja; Živanović-Mačužić, Ivana; Jeremić, Dejan; Đonović, Nela; Radunović, Aleksandar; Jovanović, Milan; Milošević, Bojan; Aleksić, Zoran; Stanković, Ivana; Vojinović, Radiša (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The most frequent form of sternal defects is a single foramen, usually located at the distal half of the sternal body, with prevalence that varies among different ethnic populations. Clinical importance of these defects arises from various diagnostic and therapeutic sternal treatments and close location of heart, lungs and other vital organs of the chest cavity. The aim of this study was to determine the prevalence and morphometric characteristics of the sternal midline foramen in the population of central Serbia. Methods. The multidetector computed tomography (MDCT) chest images of 422 patients of both genders were analyzed. The radiological imaging was performed on 64-slice MDCT scanner (Aquilion 64, Toshiba, Japan). All scans were performed in the axial plane, with subsequent multiplanar reconstruction (MPR). Due to the angulation of the sternal body coronal curved-planar, the images were obtained in order to show the whole length of the sternum and the vertical diameter of the sternal foramen. The measurements were done using the commercially available software (Imaging Software ver. 4.1.14.0, Vital-Images). Results. The solitary foramen, located in the distal segment of the sternal body, was detected in 24 patients, representing 5.9% of the observed population with slightly higher prevalence in males. The average size of foramen was 3.9 × 4.2 mm. The mean distance from the skin was 12.7 ± 3.3 mm, the distance from skin to pericardium was on average 37.3 ± 8.2 mm, while the average distance from skin to pleura was 25 ± 5.9 mm. The average depth of foramen 8.7 ± 2 mm, while the mean distance from the posterior surface of foramen to pericardium was 12.7 ± 9.1 mm. Conclusion. The results presented in this paper confirmed the prevalence of 5.9% regarding the midline sternal foramen in the observed population. Serious complications of the sternal puncture could be prevented by prior MDCT imaging.